Isolation and characterization of bioactive compounds from Euphorbia cotinifolia - B. Jayalakshmi; K. A. Raveesha; K. N. Amruthesh (SpringerOpen, 2021)
Abstract Background Green plants are found to be an effective reservoir for bioactive molecules and can provide appreciable sources of antimicrobial agents. Antibacterial activity of solvent extracts of Euphorbia cotinifolia leaves was tested by agar cup diffusion and broth microdilution methods against some common human pathogenic bacteria viz., Bacillus cereus, Klebsiella pneumonia, Enterobacter aerogenes, Escherichia coli, Staphylococcus aureus, Bacillus subtilis, and Salmonella typhi. The methanol extract of Euphorbia cotinifolia was subjected to a silica gel column, leading to the isolation of a bioactive compound 1. The structure of compounds was elucidated by spectroscopic techniques and assessed for their antibacterial activity against several human pathogenic bacteria. Results The inhibition zone ranged against some common human pathogenic bacteria was 15.25-19.50 mm, 13.50-19.25 mm, 12-18.50 mm, 15-20 mm, and 13-19 mm for ECMF1, ECMF2, ECMF3, compounds 1, respectively. The MIC was found to be in the range 91-729 μg/ml for the fractions. The inhibition range was recorded between 12-19 and 10-14 mm for methanol and ethyl acetate extracts, respectively. K. pneumoniae, E. aerogenes, and B. subtilis were highly susceptible to methanol extract with the maximum inhibition zone of 19 mm. The MIC of the compound 1 against human pathogens was 78-833 μg/ml. Conclusion The present study results suggest that tested plant extracts have moderate to potent antibacterial activity due to the occurrence of phenols and flavonoids in the extracts. The defensive property of natural antibacterials is mainly due to the presence of these major groups, vitamins, phenols, flavonoids, and carotenoids. In the present study, biologically active diterpene was isolated and the structures of the new diterpenoids isolated from E. cotinifolia were closely related to an ingenol ester.